Analysis of [FeFe]‐hydrogenase genes for the elucidation of a hydrogen‐producing bacterial community in paddy field soil. Issue 2 (11th December 2013) - Baba, Ryuko; Kimura, Makoto; Asakawa, Susumu; Watanabe, Takeshi
Abstract Hydrogen (H2) is one of the most important intermediates in the anaerobic decomposition of organic matter. Although the microorganisms consuming H2 in anaerobic environments have been well documented, those producing H2 are not well known. In this study, we elucidated potential members of H2‐producing bacteria in a paddy field soil using clone library analysis of [FeFe]‐hydrogenase genes. The [FeFe]‐hydrogenase is an enzyme involved in H2 metabolism, especially in H2 production. A suitable primer set was selected based on the preliminary clone library analysis performed using three primer sets designed for the [FeFe]‐hydrogenase genes. Soil collected in flooded and drained periods was used to examine the dominant [FeFe]‐hydrogenase genes in the paddy soil bacteria. In total, 115 and 108 clones were analyzed from the flooded and drained paddy field soils, respectively. Homology and phylogenetic analysis of the clones showed the presence of diverse [FeFe]‐hydrogenase genes mainly related to Firmicutes, Deltaproteobacteria, and Chloroflexi. Predominance of Deltaproteobacteria and Chloroflexi suggests that the distinct bacterial community possessed [FeFe]‐hydrogenase genes in the paddy field soil. Our study revealed the potential members of H2‐producing bacteria in the paddy field soil based on their genetic diversity and the distinctiveness of the [FeFe]‐hydrogenase genes.